2018
DOI: 10.1142/s0218271818500566
|View full text |Cite
|
Sign up to set email alerts
|

Tachyon warm inflation with the effects of loop quantum cosmology in the light of Planck 2015

Abstract: We investigate the observational signatures of quantum cosmology in the Cosmic Microwave Background data provided by Planck collaboration. We apply the warm inflationary paradigm with a tachyon scalar field to the loop quantum cosmology. In this context, we first provide the basic cosmological functions in terms of the tachyon field. We then obtain the slow-roll parameters and the power spectrum of scalar and tensor fluctuations respectively. Finally, we study the performance of various warm inflationary scena… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…Previous studies on both CI and WI in the context of LQC showed interesting features regarding properties of the pre-inflationary phase and the start of inflation itself [49][50][51][52][53][54][55][56][57][58]. In the present work we focus for the first time on the problem of confronting the observational predictions of WI in LQC with the latest CMB data.…”
Section: Introductionmentioning
confidence: 87%
“…Previous studies on both CI and WI in the context of LQC showed interesting features regarding properties of the pre-inflationary phase and the start of inflation itself [49][50][51][52][53][54][55][56][57][58]. In the present work we focus for the first time on the problem of confronting the observational predictions of WI in LQC with the latest CMB data.…”
Section: Introductionmentioning
confidence: 87%
“…In particular, in this work we treated the spinor fields classically, assuming them to lie at the minimal state, namely being cold. Nevertheless, incorporation of high-temperature effects, as for example in the case of warm inflation [40,41], could lead to the ap-pearance of an additional friction term, and this could further improve the values of the spectral index and the tensor-to-scalar ratio. Another possible generalization is to consider a quadratic curvature dependence, alongside the linear one, in the fermion mass, or even more general functions of the form m eff = f (m 0 , R).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated warm inflation in the LQC scenario. [49][50][51][52][53][54][55][56][57] Warm inflation in the LQC scenario was introduced first in Ref. 49, in which the dissipation coefficient Γ = constant and the number of e-folds depends on the tensor-scalar ratio r for a given scalar field mass m.…”
Section: Frameworkmentioning
confidence: 99%
“…tachyon warm inflation. 50,55,59 The existing work mainly discusses the characteristics of warm inflation in LQC scenario, but the pre-inflation dynamical behavior does not take into account. We will investigate the pre-inflation dynamical behavior of warm inflation in this paper.…”
Section: Frameworkmentioning
confidence: 99%
See 1 more Smart Citation